PENGARUH ATRIBUT PRODUK DAN WORD-OF-MOUTH TERHADAP KEPUTUSAN PEMBELIAN MELALUI BRAND IMAGE SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA PENGGUNA PRODUK MEREK EIGER DI KOTA SEMARANG) - Prihanto, Eko; Rodhiyah, Rodhiyah; Ngatno, Ngatno (Jurnal Ilmu Administrasi Bisnis, 2016)
Business development and industry that occurred lately felt more stringent and full of competition. This competition eventually forced an effort to receive a situation where they have to innovate by continue to adhere to competition. Eiger as a brand over products outdoor equipment, is trusted brand but the outdoor brand product development providers equipmentÂ  is bigger. it has been steadily declining sales especially in Semarang city. This study attempts to affect influence attributes products (X1) and word of mouth (X2) the decision to buy (Y2) through the brand image (Y1) users on brand in products eiger Semarang city. The type used is explanatory. The sample used technique combined purposive sampling and accidental sampling. The measured of scale is using likert scale. In the analysis data using the validity, reliability, a correlation coefficient, regression analysis linear multiple, the determine coefficient , t, f and sobel test by using the SPSS tools. The results show all of variable independent in this study had influence on variables depends, whether partial and simultaneous, while variable attributes products affect the purchase through the brand image mediation perfect happened and variable word-of-mouth affecting the purchase through the brand image mediation partial. For advice, making braver design again, maximize print and electronic to advertise and delivery of services sales more educate, things are useful for more interesting and ensure consumers to products that produced.